Compaction Banding in High‐Porosity Carbonate Rocks: 2. A Gradient‐Dependent Plasticity Model. Issue 12 (11th December 2020) - Abdallah, Youssouf; Sulem, Jean; Stefanou, Ioannis
Abstract: Based on the experimental study on Saint‐Maximin limestone presented in a companion paper (Abdallah et al., 2020), a gradient‐dependent plasticity model is developed to account for the key role of porosity heterogeneity in the formation and propagation of compaction bands. The constitutive law, developed in the frame of a micromorphic continuum theory, contains two hardening variables: the porosity and its second gradient. A calibration method for the additional micromechanical parameters is proposed. Data from the companion paper are used in a four‐step calibration procedure. First, the standard Cauchy component is calibrated by means of the macroscopic stress‐strain curves. An Asymmetric Cam‐Clay (ACC) model is adopted for the yield surface. The dominant wavelength of the porosity heterogeneity of the material is evaluated by applying the fast Fourier transformation (FFT) on several porosity profiles obtained on samples before loading. This wavelength is interpreted as the material length that appears in the model. In addition to the deformation maps computed from digital volume correlation (DVC), a method that evaluates the second gradient of porosity is developed to calibrate the hardening laws. A linear stability analysis (LSA) is performed to calibrate the higher‐order elastic modulus. The constitutive model is implemented in a finite element code, and triaxial loading experiments are simulated. The numerical results are consistent with the experimental data in terms of the onset of compaction bands, their thickness, and plastic strain. The size effect of the sample is explored, and a regular band spacing, comparable to the band thickness, is obtained. Key Points: The key role of porosity heterogeneity in compaction banding of a weak limestone is modeled using gradient‐dependent plasticity The constitutive model is calibrated from triaxial experiments data combined with imaging techniques to compute porosity and strain maps Finite element simulations can correctly reproduce the dominant features of the compaction bands as observed in the experiments